An atomic model of the tropomyosin cable on F-actin - Orzechowski, Marek; Li, Xiaochuan (Edward); Fischer, Stefan; Lehman, William (Biophysical journal, 2014)
Tropomyosin regulates a wide variety of actin filament functions and is best known for the role that it plays together with troponin in controlling muscle activity. For effective performance on actin filaments, adjacent 42-nm-long tropomyosin molecules are joined together by a 9- to 10-residue head-to-tail overlapping domain to form a continuous cable that wraps around the F-actin helix. Yet, despite the apparent simplicity of tropomyosin’s coiled-coil structure and its well-known periodic association with successive actin subunits along F-actin, the structure of the tropomyosin cable on actin is uncertain. This is because the conformation of the overlap region that joins neighboring molecules is poorly understood, thus leaving a significant gap in our understanding of thin-filament structure and regulation. However, recent molecular-dynamics simulations of overlap segments defined their overall shape and provided unique and sufficient cues to model the whole actin-tropomyosin filament assembly in atomic detail. In this study, we show that these MD structures merge seamlessly onto the ends of tropomyosin coiled-coils. Adjacent tropomyosin molecules can then be joined together to provide a comprehensive model of the tropomyosin cable running continuously on F-actin. The resulting complete model presented here describes for the first time (to our knowledge) an atomic-level structure of αα-striated muscle tropomyosin bound to an actin filament that includes the critical overlap domain. Thus, the model provides a structural correlate to evaluate thin-filament mechanics, self-assembly mechanisms, and the effect of disease-causing mutations.
Gesehen am 15.09.2020